2014
DOI: 10.1002/ar.22941
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriocin Sublancin Attenuates Intestinal Injury in Young Mice Infected With Staphylococcus aureus

Abstract: Sublancin, a bacteriocin, has bactericidal activity against a broad spectrum of gram-positive bacteria. However, studies have not been conducted to determine its in vivo efficacy against potential pathogens. The objective of this study was to investigate the effects of sublancin in a Staphylococcus aureus (S. aureus) infected mouse model which induced intestinal injury. A total of 160, 4-week-old mice were randomly assigned to one of eight treatments. Mice in the control group were injected intraperitoneally w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…Nisin is known to effectively inhibit numerous Gram-positive bacteria, leading to its usage in the food industry [40][41][42]. Similarly, nukacin ISK-1, produced by Staphylococcus warneri, inhibits cell wall synthesis by binding lipid II but it has not been shown to induce pore formation [43][44][45].…”
Section: Page 8 Of 40mentioning
confidence: 99%
“…Nisin is known to effectively inhibit numerous Gram-positive bacteria, leading to its usage in the food industry [40][41][42]. Similarly, nukacin ISK-1, produced by Staphylococcus warneri, inhibits cell wall synthesis by binding lipid II but it has not been shown to induce pore formation [43][44][45].…”
Section: Page 8 Of 40mentioning
confidence: 99%
“…It is capable of killing several species of Gram-positive bacteria, such as Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA) (12). Sublancin is encoded by the sunA gene on the SP␤ prophage as a prepeptide (13).…”
mentioning
confidence: 99%
“…Although the minimum inhibitory concentration (MIC) of sublancin was much higher than that of traditional antibiotics in vitro , it was demonstrated that sublancin was effective against Clostridium perfringens induced necrotic enteritis in broilers (16). We also found that sublancin has potential for prevention of S. aureus infection in mice (17). Moreover, sublancin was further found to protect against drug-resistant bacteria in a mouse MRSA infection model (18).…”
mentioning
confidence: 76%
“…Sublancin, produced by Bacillus subtilis 168, has been studied extensively for its antibacterial mechanisms (30, 31). Following our previous studies of the anti-infective efficacy of sublancin in several in vivo infection models (16, 17), we examined its role and anti-infection mechanism in a mouse model of MRSA-induced sublethal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation